Financial Fragility and the Fiscal Multiplier - Sweder van Wijnbergen; Christiaan van der Kwaak (Tinbergen Institute, 2014)
We investigate the effectiveness of `Keynesian' fiscal stimuli when government deficits and debt rollovers are (possibly partially) financed by balance sheet constrained financial intermediaries. Because financial intermediaries operate under a leverage constraint, deficit financing of fiscal stimulus packages will cause interest rates to rise as private loans are crowded out by government debt in the credit provision channel. This lowers investment and (future) capital stocks, which affects output negatively for a prolonged period. Anticipations of these future consequences cause the price of capital and bonds to drop immediately when the policy is announced, inflicting capital losses on banks which leads to further tightening of leverage constraints and credit market conditions. This balance sheet effect triggers a negative amplification cycle further lowe ring the fiscal multiplier. Longer maturity debt leads to larger capital losses and lower Keynesian multipliers. When in addition sovereign default risk is introduced, additional capital losses may occur and outcomes deteriorate further after a deficit financed stimulus package, eventually implying a cumulative Keynesian multiplier close to zero or even negative. We do not argue that multipliers are always negative; but financial fragility and sovereign risk problems may severely lower them, possibly to the point of becoming negative.
Keywords: E44; E62; H30; 330; Financial Intermediation; Macrofinancial Fragility; Fiscal Policy; Sovereign Default Risk